Adverse drug reactions in some African herbal medicine: literature review and stakeholders’ interview - Bernard Kamsu-Foguem; Clovis Foguem (Integrative Medicine Research)
Background: In view of the large consumption of herbal medicine in Africa countries, it is likely that many adverse drugs reactions go unrecorded with either patients failing to present to health services, or no pharmacovigilance analysis being made, or the analysis not being reported centrally. This problem is of interest especially for those who are working in the general area of adverse drug reactions or stakeholders in the domain of herbal medicine for considering safety issues. Methods: We are particularly interested in the way that the use of very well-known and highly valued plants is linked to the observation of adverse drug reactions in African countries. We investigated, through a literature review and using the Internet (with a semantic search strategy), some well-known or popular medicinal plants used in African herbal medicine (AHM). Other information on the properties related to use, and characteristics of medicinal plants was complemented by some interviews with stakeholders. Results: Although substantial progress has been made in elucidating the mechanisms of action of many drugs, the pharmacological actions of many medicinal plants are generally not well understood. The results of a literature review suggest that the reported adverse drug reactions of herbal remedies are often due to a lack of understanding of their preparation and appropriate use. The results of stakeholders’ interviews suggest that there is a growing need to provide patients with correct information about the herbal medicines they consume. Conclusion: An important aspect of herbal medicine is the correct, timely, and integrated communication of emerging data on risk as an essential part of pharmacovigilance, which could actually improve the health and safety of patients. This calls for improved collaboration between traditional practitioners and modern healthcare professionals, researchers, and drug regulatory authorities. In addition, there is a need for an adverse drug reaction reporting system to facilitate the collection, monitoring, and evaluation of adverse drug events.